Close Reading of Bush Studies - Syofyan, Donny (Krinok:Jurnal Linguistik Budaya, 2023)
This research attempts to address problems on how an Indonesian critic would interpret class and gender in postcolonial Australian literature. Such points of view would focus on how Indonesian critics regard class and gender issues in postcolonial Australian literature, and how it is understood by Indonesian critics. Furthermore, how Baynton’s and Franklin’s works challenge the status quo is investigated, and how to Indonesian and Australian points of view deal with class and gender concerns when reading these works. The original contribution that this research would make to this field of expertise will involve exploring the various ways different cultures examine literature and media from cultures not their own, especially as Indonesia and Australian, though both patriarchal, are very different cultures who approach gender differently.